The influence of polar heterogeneous processes on reactive chlorine at middle latitudes - Three dimensional model implications - Douglass, Anne R.; Rood, Richard B.; Kaye, Jack A.; Stolarki, Richard S.; Allen, Dale J. (1991)
Three-dimensional model calculations with the NASA/GSFC chemistry and transport model have been designed to consider the impact of heterogeneous processes occurring on polar stratospheric clouds (PSCs) in the Arctic vortex on the HCl distribution. By examining the HCl concentration for a calculation with PSCs relative to a calculation with gas phase chemistry only, the impact of polar processing on reactive chlorine species at middle latitudes is inferred. Results from the chemistry and transport model reproduce basic features of the ClO measurements (Toohey et al., 1991), which were made on the ferry flights of the ER-2 from Stavanger, Norway to Moffett Field, California via Wallops Island, Virginia on February 20 and 21, 1989. The model indicates that perturbed air which is contained within the polar vortex during winter is not homogeneously mixed, and that the ferry flights were made through air with the largest conversion of HCl to reactive chlorine that is seen at middle latitudes.